Assessment of Cross-Section Interval Variations for Earthwork Volume Estimation on Straight and Curved Road Alignments - Muhammad Afan Akbar; Meraty Ramadhini; Ongky Anggara (Journal of Applied Geospatial Information, 2026)
Cross-sectional interval variations on cut and fill volume estimation for straight and curved road alignments. Unlike previous studies that focused on a single road geometry, this study compares straight and curved road sections under identical survey conditions. Data were collected using an Electronic Total Station with cross-sectional intervals of 10 m, 25 m, and 50 m, representing dense, moderate, and sparse survey sampling scenarios commonly applied in road construction projects. Earthwork volumes were calculated using the Average End Area method based on SWDTM, Microsoft Excel, and AutoCAD Civil 3D. A paired sample t-test was applied to evaluate the significance of volume differences among interval scenarios. The results show that larger cross-sectional intervals produced greater discrepancies in cut and fill volume calculations. On straight road sections, estimated fill volumes ranged from 237.050 m³ to 254.250 m³, while on curved road sections they ranged from 333.100 m³ to 360.250 m³. Statistical analysis indicated that all calculated t-values were lower than the critical t-value at the 95% confidence level, suggesting that interval variations did not produce statistically significant differences in calculated volumes. However, wider intervals generated larger practical discrepancies and relative errors. These findings indicate that a 25 m cross-sectional interval provides a practical balance between survey efficiency and earthwork volume estimation reliability for road construction projects.